Aqueous battery low-temperature high-entropy electrolyte and preparation method thereof
By designing a low-temperature high-entropy electrolyte containing a specific ratio, the problem of electrolyte freezing and zinc dendrites in zinc ion batteries in low temperature environments is solved, and the normal battery is achieved under -20℃ low temperature environment Work and long cycle stability.
Patent Information
- Application Number
- CN202411517492.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
The electrolyte of aqueous zinc ion batteries is prone to freeze under low temperature environments, causing the battery to fail to work, and the surface of zinc negative electrode is severe, which is prone to zinc dendrites to puncture the separator, and hydrogen evolution reaction produces hydrogen, causing the battery to expand.
A low-temperature high-entropy electrolyte of aqueous battery is designed, and its raw materials include zinc sulfate, D-trehalose, α-cyclodextrin, methanol, ethylene glycol and water. Through specific proportions and preparation methods, it can be formed at -20 Electrolyte that works normally under low temperature environment ℃.
The electrolyte will not freeze at all under an environment of -20℃, which significantly improves the low-temperature performance of aqueous zinc ion batteries, reduces the formation of zinc dendrites, and improves the corrosion resistance and cycle stability of the battery.
Smart Images

Figure CN119447510A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to an aqueous battery low-temperature high-entropy electrolyte and a preparation method thereof. Background Art
[0002] Large-scale deployment of renewable energy is considered an inevitable trend to cope with the growing consumption of fossil energy and climate and environmental issues. Aqueous zinc-ion batteries have inherent advantages such as low cost, high safety, and easy access, but zinc-ion batteries also face some challenges, mainly including:
[0003] (1) The side reactions on the surface of the zinc negative electrode are serious, which easily produces zinc dendrites that pierce the diaphragm, and the hydrogen evolution reaction produces hydrogen, causing the battery to swell;
[0004] (2) The chemical stability and electrochemical stability of the electrolyte are low;
[0005] (3) Especially in low temperature environments, the electrolyte easily freezes and causes the battery to stop working. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a simple, effective and environmentally friendly low-temperature high-entropy electrolyte for aqueous batteries and a preparation method thereof; the electrolyte can work normally in a low-temperature environment of -20°C, and effectively improve the low-temperature performance of aqueous zinc-ion batteries.
[0007] To achieve the above purpose, the technical solution designed by the present invention is as follows:
[0008] The invention provides a low-temperature high-entropy electrolyte for an aqueous battery. The raw materials of the electrolyte include, by weight, 12 to 25 parts of zinc sulfate, 0.5 to 2.5 parts of D-trehalose, 0.2 to 0.8 parts of α-cyclodextrin, 0.5 to 4 parts of methanol, 2 to 12 parts of ethylene glycol and 5 to 20 parts of water.
[0009] Furthermore, the raw materials of the electrolyte include, by weight, 15 to 22 parts of zinc sulfate, 1 to 3 parts of D-trehalose, 0.2 to 0.3 parts of α-cyclodextrin, 1 to 3 parts of methanol, 2 to 12 parts of ethylene glycol and 8 to 15 parts of water.
[0010] Furthermore, the raw materials of the electrolyte include, by weight, 17.25 parts of zinc sulfate, 1.2 parts of D-trehalose, 0.25 parts of α-cyclodextrin, 1.2 parts of methanol, 4.9 parts of ethylene glycol, and 11.0 parts of deionized water.
[0011] The present invention also provides a method for preparing the above-mentioned low-temperature high-entropy electrolyte for aqueous batteries, comprising the following steps:
[0012] 1) Weigh zinc sulfate, D-trehalose, α-cyclodextrin, methanol, ethylene glycol and water according to weight ratio;
[0013] 2) dissolving zinc sulfate in water to prepare a zinc sulfate solution;
[0014] 3) firstly, adding D-trehalose to the zinc sulfate solution, stirring until completely dissolved, then adding α-cyclodextrin, stirring until completely dissolved, to obtain a dispersion;
[0015] 4) Adding methanol and ethylene glycol to the above dispersion, stirring until the solution becomes clear, thereby obtaining a low-temperature high-entropy electrolyte for an aqueous battery.
[0016] Furthermore, in the step 2), the molar concentration of the zinc sulfate solution is 2M.
[0017] Furthermore, in the step 3), the stirring temperature is 40-60°C.
[0018] The present invention also provides an application of the above-mentioned low-temperature high-entropy electrolyte for aqueous batteries in preparing batteries.
[0019] Furthermore, the battery is a zinc symmetrical battery or a full battery.
[0020] Principle of the present invention:
[0021] The essence of the freezing of electrode liquid at low temperature is the crystallization and growth process of water molecules. According to the Gibbs function:
[0022] ΔG = ΔH - TΔS;
[0023] Where ΔG is Gibbs free energy, ΔH is phase change enthalpy, T is thermodynamic temperature, and ΔS is phase change entropy;
[0024] When the system is in a solid-liquid equilibrium state, the freezing point of the solution is proportional to the phase change enthalpy and inversely proportional to the phase change entropy when other conditions remain unchanged. When other conditions remain unchanged, the freezing point of the solution can be effectively reduced by increasing the entropy of the system. Lowering the freezing point of the electrolyte can effectively improve the low-temperature performance of aqueous zinc-ion batteries.
[0025] Beneficial effects of the present invention:
[0026] 1. The electrolyte prepared by the present invention will not freeze at all under -20°C environment. DSC test shows that the freezing point of single additive and high entropy electrolyte is lower than that of pure ZnSO4 electrolyte ( Figure 1 ), which is consistent with the theoretical prediction of entropy increase-freezing point depression. After a series of tests, its corrosion resistance and hydrogen evolution inhibition effect are greatly improved compared with pure ZnSO4 electrolyte ( Figure 2). Through SEM scanning, it can be seen that HE electrolyte effectively improves the deposition of Zn on the positive electrode surface, which is a regular plane rather than a three-dimensional accumulation, and it is less likely to form zinc dendrites ( Figure 5 ).
[0027] 2. Compared with traditional additives, the zinc salt used is low in cost, the additives used are environmentally friendly, the dosage is small, the entire preparation process can be carried out at room temperature, the process is simple, the finished product has excellent antifreeze effect, it is suitable for large-scale industrial production and is easy to commercialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Optical photographs of electrolyte D5 (i.e., 2M ZnSO4 solution (pure ZnSO4)) compared with electrolytes 1 to 3 of Examples from room temperature to -20°C;
[0029] Figure 2 Optical photographs comparing the states of electrolyte D5 (i.e., 2M ZnSO4 solution (pure ZnSO4)), electrolyte D1, and electrolyte 1 from room temperature to -20°C;
[0030] Figure 3 DSC tests were performed on electrolyte 1, electrolyte D1, and electrolyte D5;
[0031] Figure 4 The Tafel curve test diagrams were performed at room temperature using electrolyte 1 and electrolyte D5 respectively;
[0032] Figure 5 The curves of LSV test at room temperature were respectively performed using electrolyte 1 and electrolyte D5;
[0033] Figure 6 A comparison of the cycle curves of the symmetrical battery assembled using electrolyte 1 and electrolyte D5 during the cooling process from 25°C to -40°C;
[0034] Figure 7 Comparison of cycle curves of symmetrical batteries assembled using electrolytes D1, D2, D3, and D4 at -20°C;
[0035] Figure 8 Long cycle diagram of the symmetric battery assembled with electrolyte 1 at -20°C;
[0036] Fig. 9 After the assembled batteries with electrolyte 1 and electrolyte D1 were cycled at -20°C for 50 hours, SEM pictures were taken using the positive electrode sheet.
[0037] Fig.10 The graph is a comparative cycle curve of a symmetrical battery using electrolyte 1 and electrolyte 3 of the embodiment at -20°C;
[0038] Fig.11 and Fig.12 The graphs are the long cycle curves and charge and discharge curves of the full battery assembled using the electrode solution 1 of Example at -20°C. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand.
[0040] Example 1
[0041] The raw materials of the aqueous battery low-temperature high-entropy electrolyte 1 are 17.25g of zinc sulfate (6H2O·ZnSO4 on the market), 1.2g of D-trehalose, 0.25g of α-cyclodextrin, 1.2g of methanol, 4.9g of ethylene glycol, and 11.0g of deionized water.
[0042] The method for preparing the above-mentioned low-temperature high-entropy electrolyte for aqueous batteries comprises the following steps:
[0043] 1) Weigh 17.25 g of zinc sulfate, 1.20 g of D-trehalose, 0.25 g of α-cyclodextrin, 1.20 g of methanol, 4.90 g of ethylene glycol, and 11.0 g of deionized water;
[0044] 2) Dissolve zinc sulfate in deionized water and stir for 6 hours until the zinc salt is completely dissolved to prepare a 2M zinc sulfate solution;
[0045] 3) firstly, adding D-trehalose to the zinc sulfate solution and stirring until completely dissolved, then adding α-cyclodextrin and stirring at a temperature of 50° C. to completely dissolve, to obtain a dispersion;
[0046] 4) Methanol and ethylene glycol were added to the above dispersion, and the mixture was stirred until the solution became clear, thereby obtaining a low-temperature high-entropy electrolyte 1 for aqueous batteries.
[0047] Example 2
[0048] The raw materials of low-temperature high-entropy electrolyte 2 for aqueous batteries are 17.25g of zinc sulfate (6H2O·ZnSO4 on the market), 0.60g of D-trehalose, 0.10g of α-cyclodextrin, 0.60g of methanol, 2.50g of ethylene glycol, and 11.0g of deionized water.
[0049] Example 3
[0050] The raw materials of the aqueous battery low-temperature high-entropy electrolyte 3 are 17.25g of zinc sulfate (6H2O·ZnSO4 on the market), 2.40g of D-trehalose, 0.50g of α-cyclodextrin, 2.40g of methanol, 10.0g of ethylene glycol, and 11.0g of deionized water.
[0051] Comparative Example 1
[0052] 17.25 g of zinc sulfate was dissolved in 11.0 g of deionized water, and the mixture was stirred for 6 h until the zinc salt was completely dissolved to prepare a 2M ZnSO4 solution; then 4.90 g of ethylene glycol was added, and the mixture was stirred until the solid was completely dissolved to obtain electrolyte D1.
[0053] Comparative Example 2
[0054] Dissolve 17.25 g of zinc sulfate in 11.0 g of deionized water, stir for 6 h until the zinc salt is completely dissolved, and prepare a 2M ZnSO4 solution; then add 1.20 g of methanol and stir for more than 2 h until it is completely dissolved to obtain electrolyte D2.
[0055] Comparative Example 3
[0056] Dissolve 17.25 g of zinc sulfate in 11.0 g of deionized water and stir for 6 h until the zinc salt is completely dissolved to prepare a 2M ZnSO4 solution; then add 1.20 g of D-trehalose and completely dissolve it to obtain electrolyte D3.
[0057] Comparative Example 4
[0058] Dissolve 17.25 g of 7H2O·ZnSO4 in 11.0 g of deionized water, stir for 6 h until the zinc salt is completely dissolved, and prepare a 2M ZnSO4 solution; then add 0.25 g of α-cyclodextrin, stir at 50°C for 2 h, and completely dissolve to obtain electrolyte D4.
[0059] Comparative Example 5
[0060] The electrolyte D5 is a 2M ZnSO4 solution prepared by dissolving 7H2O·ZnSO4 in deionized water.
[0061] Embodiments 4 to 6
[0062] A metal zinc sheet was used as the positive and negative electrodes of the symmetrical battery, and a glass cellulose separator was used as the separator. The electrolytes 1 to 3 prepared in the above examples were taken and 75 μL was added to the separators respectively to assemble zinc symmetrical batteries 1 to 3 (referred to as batteries 1 to 3).
[0063] Comparative Examples 6 to 10
[0064] A metal zinc sheet was used as the positive and negative electrodes of the symmetrical battery, and a glass cellulose separator was used as the separator. The electrolytes D1 to D5 prepared in the above comparative example were taken, and 75 μL was respectively added to the separator to assemble the zinc symmetrical batteries D1 to D5.
[0065] 1. Comparison of the test of electrolytes 1 to 3 prepared in the above examples 1 to 3 and electrolytes D1 to D5 prepared in comparative examples 1 to 5
[0066] ①Electrolyte antifreeze performance test
[0067] Electrolytes 1, 3, D1 and D5 were placed at room temperature and -20°C for 24 hours respectively.
[0068] The results are as follows Figure 1 As shown, only electrolytes 1 and 3 did not freeze; then the low-temperature performance of electrolyte 1, electrolyte D1 and electrolyte D5 was tested in the same way. Only electrolyte 1 could remain liquid at -20°C, while the other electrolytes were frozen.
[0069] The results are as follows Figure 2 As shown, only electrolyte 1 did not freeze, indicating that it has good antifreeze performance.
[0070] ② Freezing point test of different electrolytes
[0071] DSC tests were performed on electrolyte 1, electrolyte D1 and electrolyte D5.
[0072] The results are as follows Figure 3 As shown: the freezing point of electrolyte 1 is much lower than that of other electrolytes, which means that the temperature at which electrolyte 1 can be normally used is wider.
[0073] ③Corrosion resistance test of different electrolytes
[0074] In order to further test the performance of the electrolyte, anti-corrosion tests were carried out on electrolyte 1 and electrolyte D1.
[0075] like Figure 4 The Tafel curve and Figure 5 As shown in the CA curve: the corrosion current of electrolyte 1 is smaller than that of electrolyte D1, and the deposition potential of electrolyte 1 is higher than that of electrolyte D1.
[0076] In summary: compared with pure ZnSO4 electrolyte and electrolyte D1, electrolyte 1 is more excellent in low-temperature antifreeze performance and corrosion resistance.
[0077] 2. Assembled battery test
[0078] The battery was placed in a thermostat at -20°C, the cut-off voltage was between 0.5 and 1.6 V, and the test condition was 1 mA cm -2 , 1mAh cm -2 At the same time, a full battery was also assembled, with an iodine positive electrode as the positive electrode, a test cutoff voltage of 0.5-1.6V, and a cycle at a current density of 1C.
[0079] ①Comparison of different temperature tests between battery 1 and battery D5
[0080] Battery 1 and Battery D5 were tested, starting at room temperature of 25°C, then cooled to 10°C, 0°C, -10°C, -20°C, -30°C and -40°C.
[0081] The results are as follows Figure 6 As shown, even at a low temperature of -40°C, the battery 1 can cycle normally, but the cycle is most stable at -20°C, and the polarization is relatively small, so the test temperature is selected at -20°C.
[0082] ②Battery 1, D1~D4 cycle performance test
[0083] The cycle performance of batteries 1, D1 to D4 was tested at -20°C.
[0084] The results are as follows Figures 7-8 As shown, battery D1 can cycle for about 180 h, batteries D2, D3 and D4 can hardly cycle, and battery 1 can stably cycle for more than 2400 h at -20°C.
[0085] ③SEM of positive electrode sheet
[0086] The results are as follows Fig. 9 As shown in the SEM photograph, the surface of the positive electrode sheet of electrolyte 1 after low-temperature cycling is smooth and flat, and zinc dendrites are not easily grown. However, there are many flaky zinc deposits on the surface of the positive zinc sheet corresponding to electrolyte D1, which can easily lead to the growth of zinc dendrites, and further cause the battery to fail and fail to work.
[0087] ④Compare the cycles of the batteries assembled with electrolyte 1 and electrolyte 3.
[0088] The results are as follows Fig.10 As shown, although the battery 3 assembled with the electrolyte 3 can be circulated, the polarization of the battery becomes larger, which increases the cost and is very unfavorable for the long cycle of the battery.
[0089] ⑤Full battery test
[0090] Finally, a Zn / I full battery was assembled using electrolyte 1, which could stably cycle for more than 1000 h at -20°C.
[0091] like Fig.11 and Fig.12 As shown, the full battery can operate stably at -20°C with a high capacity retention rate, further revealing the practicability of the electrolyte 1 of the invention.
[0092] In summary: the electrolyte of the present invention has low cost, environmentally friendly additives, and corrosion resistance. The battery assembled using electrolyte 1 has excellent performance in a low temperature environment, can stably cycle for more than 2400 hours at -20°C, and can cycle at a minimum of -40°C. At the same time, it is not easy to form zinc dendrites, the full battery cycle is stable, and the capacity retention rate is high, which is conducive to industrialization.
[0093] Although the above embodiments have been described in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all belong to the protection scope of the present invention.
Claims
1. A low-temperature high-entropy electrolyte for an aqueous battery, characterized in that: The raw materials of the electrolyte include, by weight, 12 to 25 parts of zinc sulfate, 0.5 to 2.5 parts of D-trehalose, 0.2 to 0.8 parts of α-cyclodextrin, 0.5 to 4 parts of methanol, 2 to 12 parts of ethylene glycol and 5 to 20 parts of water.
2. The aqueous battery low-temperature high-entropy electrolyte according to claim 1, characterized in that: The raw materials of the electrolyte include 15 to 22 parts of zinc sulfate, 1 to 3 parts of D-trehalose, 0.2 to 0.3 parts of α-cyclodextrin, 1 to 3 parts of methanol, 2 to 12 parts of ethylene glycol and 8 to 15 parts of water by weight.
3. The aqueous battery low-temperature high-entropy electrolyte according to claim 1, characterized in that: The raw materials of the electrolyte include, by weight, 17.25 parts of zinc sulfate, 1.2 parts of D-trehalose, 0.25 parts of α-cyclodextrin, 1.2 parts of methanol, 4.9 parts of ethylene glycol, and 11.0 parts of deionized water.
4. A method for preparing a low-temperature high-entropy electrolyte for an aqueous battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Weigh zinc sulfate, D-trehalose, α-cyclodextrin, methanol, ethylene glycol and water according to weight ratio; 2) dissolving zinc sulfate in water to prepare a zinc sulfate solution; 3) firstly, adding D-trehalose to the zinc sulfate solution, stirring until completely dissolved, then adding α-cyclodextrin, stirring until completely dissolved, to obtain a dispersion; 4) Adding methanol and ethylene glycol to the above dispersion, stirring until the solution becomes clear, to obtain a low-temperature high-entropy electrolyte for an aqueous battery.
5. The preparation method according to claim 4, characterized in that: In the step 2), the molar concentration of the zinc sulfate solution is 2M.
6. The preparation method according to claim 4, characterized in that: In the step 3), the stirring temperature is 40-60°C.
7. Use of the low-temperature high-entropy electrolyte for aqueous batteries according to claim 1 in preparing batteries.
8. The use according to claim 7, characterized in that: The battery is a zinc symmetrical battery or a full battery.